Primary production of phytoplankton and the trophic status of the Northern Caspian - G. M. Abdurakhmanov; V. P. Ivanov; E. A. Sokol'skaya; A. G. Pankov; V. N. Vinnikova; A. F. Sokol'skiy (Юг России: экология, развитие)
Long-term materials on primary production of phytoplancton of the Northern Caspian sea are considered. The reasons of the fishery production decrease and its trophic status are specified.